BASIC WAYS OF IMPROVING PROFESSIONAL AND PEDAGOGICAL TRAINING OF FUTURE MASTERS IN ECONOMICS AND ENTREPRENEURSHIP - Погоріла, С. Г. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The basic ways of forming of masters in economics and entrepreneurship as future teachers of higher school are examined in the article. The description of necessary qualities for scientific and pedagogical workers is given. This research provides theoretical analysis of professional and pedagogical training problems of masters in economics and entrepreneurship and proves its practicability in view of rising requirements to competent specialist’s training